2016
DOI: 10.4018/ijsse.2016100103
|View full text |Cite
|
Sign up to set email alerts
|

Where to Integrate Security Practices on DevOps Platform

Abstract: “Software security” often evokes negative feelings amongst software developers because this term is associated with additional programming effort, uncertainty and road blocker activity on rapid development and release cycles. The Secure DevOps movement attempts to combat the toxic environment surrounding software security by shifting the paradigm from following rules and guidelines to creatively determining solutions for tough security problems (Taschner, 2015). Secure software should be focused on a proactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…Impact: explores how DevOps effects other aspects of software development such as architecture [42], security [49], quality assurance [40], or the impact of DevOps on software development in specific scenarios, such as the development of software for research [12].…”
Section: Peer-reviewed Literaturementioning
confidence: 99%
“…Impact: explores how DevOps effects other aspects of software development such as architecture [42], security [49], quality assurance [40], or the impact of DevOps on software development in specific scenarios, such as the development of software for research [12].…”
Section: Peer-reviewed Literaturementioning
confidence: 99%
“…Challenge of unrestricted collaboration [20], [23], [58], [79] CH12 Using unsuitable performance metrics for security evaluation [2], [69], [78], [79] CH13 Abundance of information is a serious threat to secure data [60], [62], [80] CH14 Use of immature automated deployment tools [61], [81], [82] CH15 Inadequate channel to monitor the collaboration of teams [52], [53], [71], [79]…”
Section: Ch11mentioning
confidence: 99%
“…Therefore, there should be proper automation testing tools to monitor the security risks of DevOps. As we are dealing with heterogeneous nature in an organization all sites must coordinate to resolve any ambiguity on time [52,61]. CH16 "lack of secure coding standards" is considered as the challenging factor in terms of DevOps security.…”
Section: Application Of Promethee II Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…• Use of immature automated deployment tools (2) • Use of unsuitable metrics (2) • Insufficient monitoring of collaboration (1) Mohan and ben Othmane [17] attempted to perform a mapping study on security in DevOps, but found very few primary studies; mostly trade conference presentations and blogs (similar to the artifacts above). Yasar and Kontostathis [25] propose focusing on security requirements, threat modeling, environment configuration, static analysis, code review, penetration testing, environment testing, and finally a manual security review. They claim that quick incident response is an implicit benefit of such an approach, but do not offer any empirical evidence to support the claim.…”
Section: Devops Security In the Literaturementioning
confidence: 99%